Supply chain management in the course of time - A systematisation of past, present and future objectives - Anna-Maria Nitsche; Wibke Kusturica; Denis Neumann; Christian-Andreas Schumann; Christoph Laroque (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: Supply chain management (SCM) has undergone a transformation since its origins in the 1990s as ecological considerations have influenced SCM goals in recent years. This systematic literature review of a preliminary sample of 2,471 publications aims to show how target design has changed over time. Methodology: The systematic literature review is based on Tranfield et al. (2003) and Denyer and Tranfield (2009). Following extraction from the Scopus database and multiple screenings, the top 100 academic publications with the highest yearly average citations from the periods 1996 to 2000 and 2016 to 2020 are included in the analysis. Findings: To highlight similarities and differences, the current and initial goals of SCM are assigned to one of the sustainability dimensions: ecological, economic, social. By comparing the publications at the time of the initial emergence of SCM and the current period, a significant shift in the main objectives of SCM could be derived. Originality: This compact structured analysis and discussion of the change in SCM objectives helps to comprehend past developments, to understand current challenges, and to assess future trends. Furthermore, the comparison of the two periods provides a unique perspective on the development of the research field of SCM.
urn:nbn:de:gbv:830-882.0162389; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; Sustainability